PD-L1 monoclonal antibody alleviated MI injury of left ventricular function via modulating CD47/SHP2/SIRPα/SYK/FcγR signalings in tumor associated macrophages - Deyou Kong; Yongzhen Chen; Yajuan Yin; Zhikun Liu; Fang Yang; Xiaohong Li; Dongxing Shen; Jun Zhang (Scientific Reports)
Abstract To investigate how PD-L1 monoclonal antibodies (mAbs) affect the left ventricular function in mice with myocardial infarction (MI) and through what mechanisms they exert their effects. In vivo experiments were conducted using 27 female BALB/c mice, which were divided equally into 3 groups. Cardiac function was assessed by ultrasound. Heart tissue and breast cancer tumor samples were isolated, and the content of cGAMP was measured using LC-MS/MS. The extent of myocardial infarction was evaluated by Masson staining. In vitro experiments involved dividing macrophages, treated with different inducers, into 8 groups. Protein expression levels in each group were analyzed by Western blotting, and the macrophages were transplanted into experimental mice for observation. In the in vivo experiments, ultrasound examination showed that PD-L1 mAb improved cardiac function in mice with breast cancer and MI. Both cGAMP content measurement and Masson staining results indicated that PD-L1 mAb had a therapeutic effect on mice with breast cancer and MI, improving the infarct condition and slowing tumor progression. In vitro Western blotting analysis revealed that PD-L1 mAb can modulate the CD47/SHP2/SIRPα/SYK/FcγR signaling pathway, thereby affecting breast cancer. Treatment with a STING inhibitor significantly reduced the cGAMP effect, leading to improved left ventricular function in mice with MI. PD-L1 monoclonal antibodies improve left ventricular function in mice with myocardial infarction by modulating the CD47/SHP2/SIRPα/SYK/FcγR signaling pathway in tumor-associated macrophages and inhibiting the expression of cGAMP.